The knowledge and perceptions of Attention Deficit Hyperactivity Disorder held by foundation phase educators in a Township in Gauteng. - Lazarus, Kim Jayde (My University, 2013)
Attention Deficit Hyperactivity Disorder (ADHD) is a very common disorder that affects 8% to 10% of South African children. It is thus prevalent in the classroom, and with the advent of inclusive education in South Africa, educators have to facilitate and support the needs of learners with ADHD. Educators play an integral role and provide essential information with regards to the identification, diagnosis and referral of ADHD. It is the responsibility of the educator to create an environment where every learner has the opportunity to succeed. However, uncertainty exists as to whether South African educators have an appropriate and adequate understanding of the disorder. This study therefore aimed to examine the knowledge and perceptions of ADHD held by foundation phase educators in a township in Gauteng. A sample of 100 female educators was used in the study and a mixed methods approach using a questionnaire was administered to the educators. Their knowledge and perceptions in the three content areas of ADHD (Associated Features, Symptoms/Diagnosis and Treatment) was explored. Data analysis reflected that the educators in the sample had inadequate and insufficient knowledge and understandings of ADHD. Educators seemed to know the most about the symptoms of the condition, less about the associated features and the least about treatment approaches. The implications of these research findings are discussed, within the South African context.
Keywords: Attention Deficit Hyperactivity Disorder; Foundation phase educators; Lack of knowledge and perceptions of Attention Deficit Hyperactivity Disorder; Educator training